(untitled) (The Nepali Mathematical Sciences Report, 2021)
In this research work, we have introduced generalized Nörlund summability of derived Fourier series and its conjugate series and utilized it to several summability method. Further, a set of new and well known arbitrary result have been obtained by using main theorem. Considering suitable conditions a previous result has been obtained, which validates the current findings.